PREVALENCE AND RELATION OF WEIGHT EXCESS AND BLOOD PRESSURE WITH ANTROPOMETRIC MEASUREMENTS IN A SAMPLE OF ITALIAN CHILDREN. (June 2018) - Tagetti, A.; Bonafini, S.; Giontella, A.; Minuz, P.; Fezzi, S.; Maffeis, C.; Antoniazzi, F.; Fava, C.
Abstract : Objective: Weight excess and hypertension represent an increasing epidemics not only in adults but even in children. The aim of the present study was to asses the prevalence of weight excess and high blood pressure (BP) and their relation with other anthropometric measurements in a school-based study. Figure. No caption available. Design and method: 309 children attending the 3rd and 4th classes of 4 primary schools (mean age 8.64 ± 0.7y) in Verona south district participated. All children underwent anthropometric and vascular measurements at school. Results: Based on the 85th and 95th percentiles of BMI, 19% of children were classified as overweight and 13% as obese, without significant gender differences. Waist/height ratio was below 0.5 in 93% of normal-weight children, 48% in overweight children and 12% in obese children. When considering the subgroup of children with weight excess (obese + overweight) in comparison to normal weight children, they showed higher systolic BP (including the z-score of systolic BP). Considering BP in the whole sample, 22% resulted above the 95th percentile and 17% between the 90th and 95th percentile whereas the prevalence of BP > 95th percentile in obese was 31%. After repetition of BP measurement in standard conditions in a subsample of 25 children with BP > 95th percentile at the first visit, only one child confirmed a BP > 95th percentile. Systolic and diastolic BP were directly correlated with BMI, waist circumference, hip circumference and waist/height ratio, but the latter showed a weaker correlation with BP in comparison to the other anthropometric characteristics. In obese children, most correlations were still significant and showed a higher correlation coefficient. Conclusions: Excess weight and high BP is frequent also in Italian children attending the primary school. Measures of adiposity and BP associate calling for preventive actions. Epidemiological studies should pay attention to standardize the conditions of measurement when the exact prevalence of hypertension has to be estimated.